ANALISIS KEGAGALAN CONNECTING ROD PADA KOMPRESOR - , RINALDY ANIS BARIZY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research discuss failure analysis of engineering material. In this research, the object under study is the connecting rod compressor that failed after operating less than 6 months. Referring to the study of materials science, the failure of a component in terms of the material can be caused by several factors, including improper material selection, defects in material, poor design, fabrication process, maintenance, and errors in determining operating conditions. The purpose of this research is to identify the cause of failure, how the failure occurs and to prevent the future occurrence of failure in the component. Therefore, the research starts from the material characterization including composition test, tensile test, hardness test, and microstructure observation . After the material characterization be discovered, this research continues towards failure analysis by using an scanning electron microscope (SEM) to study surface fractography and followed by analyzing fatigue crack growth rate. The results of this study show that the failure was fatigue due to 2 factors, first, the presence of stress concentration at rounded fillet near the big connecting rod end is responsible for crack nucleation, secondly, porosity and inclusions in material which accelerate the crack propagation when the component is subjected to dynamic load. This is due to fabrication errors where there are currently no uniform cooling during the process of casting. Keyword : connecting rod, failure analysis, fatigue, fractography